Progress in Somatic Embryogenesis of Japanese Pines - Maruyama, Tsuyoshi E.; Hosoi, Yoshihisa (Frontiers in Plant Science, 2019)
Somatic embryogenesis (SE) in not only one of the most promising techniques for mass propagation of selected trees, but also is a valuable tool for basic research studies in cell biology and genetic engineering, and it allows the long-term ex situ conservation of genetic resources by cryopreservation techniques. This review reports the most recent progress in SE, protoplast culture, and cryopreservation of four important Japanese pines (Pinus thunbergii, Pinus densiflora, Pinus armandii var. amamiana, and Pinus luchuensis). Induction of embryogenic tissues (ET), embryogenic culture maintenance/proliferation, production of somatic embryos, germination, and conversion to plants are described focusing on the protocols most commonly reported for plant production in Pinus species through to SE.